ENCYCLOPEDIA AMERICANA - Americana Corporation 641456 (New York : Americana Corporation, 1965)
VOLUME 1. A to ANNUALS -- VOLUME 2. Annuity to Azzubeydi -- VOLUME 3. B to Bird's Foot -- VOLUME 4. Birds of Paradise to Bulfinch -- VOLUME 5. Bulgaria to Castanos -- VOLUME 6. Caste to Civil Law -- VOLUME 7. Civil List to Coronium -- VOLUME 8. Corot to Deseronto -- VOLUME 9. Desert to Egret -- VOLUME 10. Egusquiza to Falsetto -- VOLUME 11. Falstaff to Francken -- VOLUME 12. Franco to Goethals -- VOLUME 13. Goethe to Haw -- VOLUME 14. Hawaii to Index of Refraction -- VOLUME 15. India to Jeffers -- VOLUME 16. Jefferson, Charles E. to Latin -- VOLUME 17. Latin America to Lytton -- VOLUME 18. M to Mexico City -- VOLUME 19. Meyer to Naval Rank -- VOLUME 20. Naval Reserve to Orleans -- VOLUME 21. Orley to Photographic Telescope -- VOLUME 22. Photography to Pumpkin -- VOLUME 23. Pumps to Russellville -- VOLUME 24. Russia to Silius -- VOLUME 25. Silk to Sulphovinic Acid -- VOLUME 26. Sulphur to Tramways, Aerial -- VOLUME 27. Trance to Venial Sin -- VOLUME 28. Venice to Wilmot, John -- VOLUME 29. Wilmot Proviso to Zygote -- VOLUME 30. Index.